APPLICATION OF THE FAILURE MODE AND EFFECT ANALYSIS METHOD IN QUALITY CONTROL OF STREET LAMP POLE PRODUCTION PROCESS IN MEDAN CITY - Muhammad Naufal Ghani Siregar; Yeni Absah; Anizar Anizar (CV. Radja Publika, 2026)
The production process for galvanized street lamp poles in Medan City involves six main stages, each of which can lead to product failures. The absence of a standardized, documented quality control system means these potential failures cannot be proactively identified or controlled. This study aims to identify potential failures, calculate Risk Priority Numbers (RPNs), and formulate quality control action recommendations using the Failure Mode and Effects Analysis (FMEA) method. The study employed a descriptive, qualitative approach with a single-case study design. Data were collected through in-depth interviews, direct observation, and documentation studies involving four key informants. The results identified eleven (11) potential failures across six production process stages. Three failures were categorized as top priority, with the highest RPN values: weld defects—porosity, undercut, and incomplete fusion (RPN 315); zinc coating thickness below the minimum standard (RPN 288); and defective products passing through to the shipping stage (RPN 280). Recommended control actions include developing standard operating procedures, implementing a welder certification program, conducting batch-by-batch zinc thickness testing, adopting standardized inspection checklists, and periodically calibrating measuring instruments.